The dark side of visual awareness in sport: Inattentional blindness in a real-world basketball task - Furley, P.; Memmert, D.; Heller, C. (Attention, Perception, & Psychophysics, 2010)
Most research in the field of decision making in sports has focused on the bright side of visual attention and has not taken the dark side of visual awareness into account. Understanding the costs of such inattention should be complementary to the study of how attention facilitates perception. In the present study, we provide evidence for the existence of inattentional blindness (IB) in a real-world basketball setting among adults (Experiment 1). In Experiment 2, we found that players with hardly any basketball experience were more likely to experience IB in a real-world basketball setting, as compared with experienced athletes. Improving the ecological validity of the setting by enhancing the perception-action coupling (Experiment 3) and increasing task difficulty (Experiment 4) did not appear to affect the occurrence of IB among experienced athletes. IB can be considered a limitation of the visual system, but it also highlights a critical aspect of visual processing, which allows us to remain focused on the important aspects of the world. But as is shown in the present experiments, it is possible to induce an attentional set—for example, by sport-specific instructions—that leads to players` missing important game-relevant information.